Labor market programs, the discouraged-worker effect, and labor force participation - Kerstin Johansson (Institute for Labour Market Policy Evaluation (IFAU), 2002)
This paper estimates the macroeconomic effect of labor market programs on labor force participation. Labor market programs could counteract business-cycle variation in the participation rate that is due to the discouraged-worker effect, and they could prevent labor force outflow. An equation that determines the participation rate is estimated with GMM, using panel data (1986-1998) for Sweden's municipalities. The results indicate that labor market programs have relatively large and positive effects on labor force participation. If the number of participants in labor market programs increases temporarily by 100, the labor force increases immediately by around 63 persons. The effect is temporary so the number of participants in the labor force returns to the old level in the next period. If the number of participants in programs is permanently increased, the labor force increases by about 70 persons in the long run. Programs are reducing the business-cycle variation in labor force participation because the effect is positive and programs are counter-cyclical and they counteract the discouraged-worker effect in the long run. The results indicate that programs could prevent labor force outflow; participants who would have left labor force in the abscence of programs are may now be participating because of the programs. Wages and vacancies have positive long- and short-run effects on participation rate. Open unemployment, the job destruction rate, and proportions of persons between ages 18-24 and 55-65 have negative long run effects on the participation rate.
Keywords: E64; J22; J68; 330; Labor supply; labor market programs; dynamic panel data